Analysis of the Relationship between Environmental, Social, and Governance (ESG) and Firm Value: A Systematic Review of Empirical Evidence in Indonesia - Dedi Hartono; Wisnu Mawardi; Sugeng Wahyudi (Politeknik Siber Cerdika Internasional, 2026)
Background: ESG is an essential non-financial factor that can influence firm value; however, the evidence in Indonesia shows mixed results because ESG activity measurements are not standardized, the market remains varied, and disclosure is not evenly distributed, so a generalizable conclusion is not available. Objective: This research seeks to systematically review empirical evidence on the effect of ESG on firm value by emphasizing the analysis in the Indonesian context. Methods: This work utilizes a Systematic Literature Review (SLR) in line with PRISMA guidelines. In March 2025, exhaustive searches were conducted on Scopus, ScienceDirect, and Google Scholar (limited to Scopus-indexed or peer-reviewed sources only), and tailored Boolean search combinations were used. Out of 487 identified records, 20 empirical studies on Indonesian and internationally benchmarked listed companies satisfied the inclusion criteria. Results: Among the 20 studies reviewed, 6 Indonesian studies found ESG–firm value effects to be positive, 3 negative, and 4 insignificant; heterogeneity is explained by industry sector, the life cycle stage of the firm, and the quality of ESG disclosure. International benchmark studies (n = 10) showed a positive and largely consistent impact, attributable to stronger regulatory frameworks and greater investor ESG awareness in developed and more mature emerging markets, which reduce firm-level risks. Conclusion: The impact of ESG on firm value is context-dependent, and Indonesia needs standardized disclosure, ESG assurance, and investor education to harness its positive impact on firm value.